Polarization Reconstruction of Cosmic Rays with the ARIANNA Neutrino Radio Detector - Zhao, Leshan; Anker, Astrid; Baldi, Pierre; Barwick, Steven W.; Beise, Jakob; Bernhoff, Hans; Besson, Dave Z.; Bingefors, Nils; Cataldo, Maddalena; Chen, Pisin; Fernández, Daniel García; Gaswint, Geoffrey; et al. (Proceedings of Science, 2022)
The ARIANNA detector is designed to detect neutrinos of energies above 1016 eV. Due to the similarities in generated radio signals, cosmic rays are often used as test beams for neutrino detectors. Some ARIANNA detector stations are equipped with antennas capable of detecting air showers. The radio emission properties of air showers are well understood, and the polarization of the radio signal can be predicted from arrival direction with high precision. For this reason, cosmic rays can be used as a proxy to assess the reconstruction capabilities of the ARIANNA neutrino detector. We report on dedicated efforts of reconstructing the polarization of cosmic-ray radio pulses. A total of 148 cosmic rays are identified from over 90,000 triggered events collected between Nov 21, 2018 and Mar 15, 2019. A cut was put on these events requiring them to have a signal-to-noise (SNR) ratio of at least 4.5 in all upward-facing channels. This was to improve the performance of arrival direction and polarization reconstruction algorithms. Polarization of these cosmic rays were reconstructed with a resolution of 3.5 degrees (68% containment), which agrees with the expected value we obtained from simulation. Furthermore, if we subselect events with zenith angle greater than 70 deg, the contribution to polarization of Askaryan effect is reduced, which reduces the error in the predicted polarization. With limited statistics, we find the polarization uncertainty is reduced to 1.3 deg (68% containment).
CRIS-Team Scopus Importer:2023-08-15